2003
DOI: 10.1111/j.1467-8381.2003.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Differentials Determinants Between Skills in the Malaysian Manufacturing Sector

Abstract: The Malaysian manufacturing sector has been experiencing a gradual change in its production process as it shifts from labor‐intensive to more capital‐intensive techniques. This has led to a change in the skills required by the industries where skilled workers are in greater demand and where the wage ratio between skills favors the skilled workers. There are many factors that can influence an indi‐vidual's earnings. These include educational attainment, job location, types of industries and sex. This paper atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…3 Other studies of Malaysia (Lim 1977), Thailand (Movshuk andMatsuoka-Movshuk 2006, Ramstetter 2004), and Venezuela and Mexico (Aitken et al 1996) have found that MNE-local wage differentials tended to persist after accounting for similar plant-level or firm-level characteristics, but were unable to account for the influences of labor force quality. In addition, Ismail and Haji Mat Zin (2003) and similar studies of workers in other economies reveal significant returns to human capital when measured by worker education, training, and experience, for example. Thus, there is substantial evidence that both plant ownership and worker quality have important influences on worker earnings.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…3 Other studies of Malaysia (Lim 1977), Thailand (Movshuk andMatsuoka-Movshuk 2006, Ramstetter 2004), and Venezuela and Mexico (Aitken et al 1996) have found that MNE-local wage differentials tended to persist after accounting for similar plant-level or firm-level characteristics, but were unable to account for the influences of labor force quality. In addition, Ismail and Haji Mat Zin (2003) and similar studies of workers in other economies reveal significant returns to human capital when measured by worker education, training, and experience, for example. Thus, there is substantial evidence that both plant ownership and worker quality have important influences on worker earnings.…”
Section: Introductionmentioning
confidence: 92%
“…Combining all 17 industries, highly educated workers (those with some kind of tertiary education) accounted for 16% of all workers in MNEs in 2000 and this share rose to 19% in 2003-2004). Similar to shares of highly paid workers, shares of highly educated workers were highest in chemicals and general machinery (averaging 30%-31%), followed by non-metallic mineral products; radio, TV, and communication machinery; and basic metals.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Poor regulation would result in overdependence, much like the case in agriculture, specifically oil palm. As the number of Indonesian workers declined, preferring to work in their own country, the productivity of the industry has suffered (Ismail & Zin, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This policy shift in public education expenditure towards vocational education at the secondary level is found to have important implications on the labour markets of the countries. Ismail and Zin (2003) found that human capital variables, particularly training, contributed 41.2% to the differentials between the skilled and the semi-skilled, 19.1% between the skilled and the unskilled, and 54.9% between the semi-skilled and the unskilled workers in the Malaysian manufacturing sector. On the other hand, there has been an increase in the share of low–medium skilled workers who received secondary vocational education in agricultural, manufacturing and non-manufacturing sectors in India (Bhattacharya et al, 2020).…”
mentioning
confidence: 99%